Dipicolylamino-methoxy-1, 2, 4, 5-tetrazine ligand and its metal complexes: Structural and photophysical studies. (15th September 2019) - Stetsiuk, Oleh; El-Ghayoury, Abdelkrim; Hauser, Andreas; Avarvari, Narcis
Graphical abstract: The synthesis and characterization of a methoxy-tetrazine-dipicolylamine ligand is reported. The corresponding zinc and cadmium complexes, for which the single crystal X-ray structures are described, show luminescence in solution while in the ligand the luminescence is quenched. Abstract: The ligand 6-methoxy-N, N-bis(pyridin-2-ylmethyl)-1, 2, 4, 5-tetrazin-3-amine (L ) has been prepared by nucleophilic substitution from 3-chloro-6-dipicolylamino-1, 2, 4, 5-tetrazine (1 ). The ligandL, together with two neutral zinc(II) and cadmium(II) metal complexes, respectively formulated as [ZnL Cl2 ] (2 ) and [CdL Cl2 ]2 (3 ), have been crystallized and analyzed by single crystal X-ray diffraction analysis. The two metal complexes are isostructural and crystallize in the monoclinic system, space group P 21 / c . The structure analysis indicates that the amino nitrogen atom is involved in semi-coordination with the metal centers, thus leading to distorted coordination geometries. Photophysical studies of the ligand and its corresponding metal complexes2 and3 show a switch-on of the luminescence upon chelation with the diamagnetic Zn(II) and Cd(II) metal ions.